Coordinating distributed energy resources during microgrid emergency operation - C. Gouveia (2014)
The development of the Smart Grid (SG) concept is the pathway for assuring flexible, reliable and efficient distribution networks while integrating high shares of Distributed Energy Resources (DER): renewable energy based generation, distributed storage and controllable loads such as Electric Vehicles (EV). Within the SG paradigm, the Microgrid (MG) can be regarded as a highly flexible and controllable Low Voltage (LV) cell, which is able to decentralize the distribution management and control system while providing additional controllability and observability. A network of controllers interconnected by a communication system ensures the management and control of the LV microgrid, enabling both interconnected and autonomous operation modes. This new distribution operation philosophy is in line with the SG paradigm, since it improves the security and reliability of the system, being able to tackle the technical challenges resulting from the large scale integration of DER and provide the adequate framework to fully integrate SG new players such as the EV. By exploiting the MG operational flexibility and controllability, this chapter aims to provide an extended overview on MG self-healing capabilities, namely on its ability of operating autonomously from the main grid and perform local service restoration. The MG hierarchical management and control structure is revisited and adapted in order to exploit the flexibility of SG new players, like the EV and flexible loads and integrate smart metering infrastructures. The implementation of the MG architecture and communication infrastructure in a laboratorial facility is also presented and used to validate the MG self-healing capabilities.